2011
DOI: 10.3112/erdkunde.2011.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Climate and land-use change as driving forces in lowland semi-natural vegetation dynamics

Abstract: In many parts of Europe, extensive changes in vegetation have taken place during recent decades. In Norway, forest expansion is a major trend, with an increase in volume of 20.3% during the period 1994-2008. The annual increase has more than doubled since 1967. This study was carried out to gain more insight into the complexity of vegetation dynamics and alterations in a lowland area on the coast of W Norway, and to identify the driving forces behind these changes. Field surveys were carried out with aerial ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…In local studies, it has been documented that many of the above-mentioned areas have been deforested by various forms of land use lasting for millennias, whereas natural forest regeneration and afforestation in recent decades have evidently shown the ecological potential for forests in semi-natural heaths and meadows throughout Norway (Bryn, 2008;Bryn & Daugstad, 2001;Bryn et al, 2010;Hemsing & Bryn, 2011;Lundberg 2011;Måren, 2009;Moen et al, 2006;Øyen, 2008;Potthoff, 2009;Rö ssler et al, 2008). Similar findings have been reported from local studies in the European Alps and many other mountain regions, so the process of deforestation is probably more or less the same for populated mountain regions worldwide, although with large variations in the extent of deforestation (GehrigFasel et al, 2007;Rutherford et al, 2008;Sitzia et al, 2010;Slaymaker, 2010;Tasser et al, 2007).…”
Section: Gis Model Of Potential Forest Expansion In Norway 89mentioning
confidence: 98%
“…In local studies, it has been documented that many of the above-mentioned areas have been deforested by various forms of land use lasting for millennias, whereas natural forest regeneration and afforestation in recent decades have evidently shown the ecological potential for forests in semi-natural heaths and meadows throughout Norway (Bryn, 2008;Bryn & Daugstad, 2001;Bryn et al, 2010;Hemsing & Bryn, 2011;Lundberg 2011;Måren, 2009;Moen et al, 2006;Øyen, 2008;Potthoff, 2009;Rö ssler et al, 2008). Similar findings have been reported from local studies in the European Alps and many other mountain regions, so the process of deforestation is probably more or less the same for populated mountain regions worldwide, although with large variations in the extent of deforestation (GehrigFasel et al, 2007;Rutherford et al, 2008;Sitzia et al, 2010;Slaymaker, 2010;Tasser et al, 2007).…”
Section: Gis Model Of Potential Forest Expansion In Norway 89mentioning
confidence: 98%
“…Even habitats in remote areas such as inland forests in northern Scandinavia (Ohlson et al 1997) and parts of the Scandinavian mountains (Austrheim & Eriksson 2001) have been utilized for a long time. Currently, regrowth after land use changes is considered to be the major driving force behind the process of forestation in lowland semi-natural vegetation and for the expansion of the forest line upwards (Bryn 2008;Lundberg 2011;Wehn et al 2012). Thus, the distinction between 'undisturbed' and 'disturbed' landscapes is not always clear, but may still be of utmost importance for conservation success.…”
Section: Ecological Consequences Of Former Land Use and Conservation mentioning
confidence: 98%
“…The modelled response curves indicate that abandonment of the habitats and cessation of domestic grazing will reduce the suitability of the areas. Earlier studies have shown that changes in grazing pressure by domestic animals in mountainous areas in Norway have caused radical vegetation shifts from open semi-natural vegetation to more forested and scrubby areas (Lundberg 2011;Vandvik and Birks 2004;Wehn 2009;Wehn, Olsson, and Hanssen 2012;Wehn, Pedersen, and Hanssen 2011). Livestock grazing supresses taller plant species (Wehn 2009) and thus allows more light for P. scandinavica to persist.…”
Section: Environmental Variablementioning
confidence: 99%
“…Norwegian semi-natural habitats have, as in other European countries, decreased due to forest expansion (Lundberg 2011;Vandvik and Birks 2004;Wehn 2009;Wehn, Olsson, and Hanssen 2012;Wehn, Pedersen, and Hanssen 2011). Approximately 40% of the species associated with alpine environments in the Norwegian National Red List are threatened because of changing land use in the alpine region (Austrheim et al 2010).…”
Section: Introductionmentioning
confidence: 99%